Pharmacobiological study in vitro and in silico of the extract of the Hypericum perforatum plant - Amrani chahrazad; Larouci aya; :Mekhieber soumia (. جامعة الوادي.Université d'EL-Oued., 2025)
This study aimed to evaluate the effectiveness of Hypericum perforatum extract, rich in bioactive compounds such as flavonoids, polyphenols, alkaloids, tannins, and cardiac glycosides, in inhibiting the cyclooxygenase-2 (COX-2) enzyme to reduce the formation of prostaglandins, key mediators in the development of fever and inflammatory responses. The anti-inflammatory activity of the extract was assessed through an in vitro assay examining the inhibition of bovine serum albumin (BSA) denaturation using UV-Vis spectroscopy, as well as via molecular docking simulations with the COX-2 enzyme. Additionally, a range of other biological activities was investigated, including anticomplement, antioxidant, anti-diabetic, antibacterial, and phagocytic activities. The study also involved the preparation of a topical cream formulation incorporating the plant extract. The extract, rich in active compounds, was integrated into a suitable cream base, taking into account diffusion and stability properties to ensure the effectiveness of the final product. The physicochemical properties of the prepared cream, such as texture, viscosity, and homogeneity, were evaluated, alongside preliminary short-term stability studies. This initial step aimed to explore the potential for transforming the promising extract into a user-friendly topical pharmaceutical product capable of providing localized relief from inflammation. The results demonstrated that the extracts possess potent anti-inflammatory activity, as evidenced by their IC50 values and negative ΔG values. The negative ΔG values indicated a strong binding affinity to the biological target, and the molecular docking results corroborated the in vitro findings. Furthermore, in simulations of the enzyme–extract interaction, the physicochemical properties, pharmacokinetics, and toxicity profiles of selected extracts were predicted using the SwissADME and ProTox servers. In conclusion, our findings confirm the effectiveness of Hypericum perforatum extract as an anti-inflammatory agent and open avenues for the development of topical formulations based on it, making it a promising candidate for future topical anti-inflammatory therapeutics.
Toxicology
Keywords: Docking; SwissADME; Cyclooxygenase-2 (COX-2); Hypericum perforatum; Anti-inflammatory ointment; phagocytic activity.